Trust, membership in groups, and household welfare: evidence from KwaZulu-Natal, South Africa - Haddad, Lawrence J.; Maluccio, John A. (International Food Policy Research Institute, 2002)
This paper explores the relationship between group membership and trust. Specifically, the authors examine (1) the importance of trust in the decision to join groups, (2) the subsequent ability of groups to generate trust, and (3) the influence of group membership and trust on a measure of well-being, per capita household income. They use longitudinal data from KwaZulu-Natal Province, South Africa, allowing them to control for potential simultaneity and measurement-error problems in the estimation. They disaggregate groups into financial and nonfinancial and “trust in people” by type of agent or actor. They can thus examine whether different types of trust are important for participating in different types of groups and whether different types of group participation are important for generating different types of trust. The research finds that (1) trust in local agents is an important determinant of membership in financial groups but not for membership in nonfinancial groups, (2) membership in both types of groups generates trust in nonlocal agents but not local agents, and (3) membership in financial and nonfinancial groups leads to higher well-being. The first two results suggest that financial groups serve a role in expanding the radius of trust, while the first and third results suggest a role for trust in improving well-being.